A Comparative Study on the Moral Conceptual Framework of Kohlberg and Wang Yangming - Zhu, Mao-ling (Cultural and religious studies, 2018)
Kohlberg constructed modern Western moral cognition theory. Wang Yangming proposed the idea of the extension of intuitive knowledge in Ming Dynasty. We conduct a comparison on three main conceptual schemes of Kohlberg’s theory—moral judgment, moral development, and moral behavior—from the following three aspects: problem consciousness, thinking model, and value idea. Moral cognition development theory lays emphasis on the core position of cognition to the moral development, while the idea of intuitive knowledge aims to become sages. From the point of view of thinking model, moral cognition development theory intents to conduct moral education for individual moral development, while the idea of the extension of intuitive knowledge highlights the intuitive knowledge ontology in the practice of extending the intuitive knowledge to its extremity and removing the obstacles of selfishness. In terms of value idea, the core value idea of moral cognition theory is the principle of justice, but the idea of the extension of intuitive knowledge indicates that the intuitive knowledge has characteristics of innateness and universality, which is the judgment principle of the individual transcendentality.